Differentiation-specific transcriptional regulation of the hepatitis B virus large surface antigen gene in human hepatoma cell lines. - Raney, A K (1990)
The transcriptional activities of the four hepatitis B virus promoters were compared in three differentiated hepatoma cell lines, HepG2, Hep3B, and PLC/PRF/5; a dedifferentiated subline of HepG2, HepG2.1; a human cervical carcinoma cell line, HeLa S3; and a mouse fibroblast cell line, NIH 3T3. The plasmid constructs, which contain the complete hepatitis B virus genome directing the expression of the luciferase reporter gene, were analyzed by transient transfection assays. The relative orders of the levels of the transcriptional activities of the four promoters were similar in each of the cell lines. The major surface antigen and X-gene promoters displayed the highest activity levels, the core promoter activity level was less than or similar to the activity levels of these two promoters, and the large surface antigen promoter had the lowest activity level in all of the cell lines examined. The core promoter demonstrated an approximately 2- to 20-fold higher relative level of expression in the differentiated hepatoma cell lines, suggesting that this promoter might be preferentially active in these cells. The relative level of activity of the large surface antigen promoter in the differentiated hepatoma cell lines was approximately 5 to 90 times greater than that observed in the other cell lines, indicating that the activity of this promoter is highly specific for differentiation state and cell type. Deletion analysis of the large surface antigen promoter demonstrated that the sequence element responsible for the differentiation state-specific expression from this promoter is located between nucleotides 2719 and 2733 (-90 and -76). Within this sequence element is a binding site (GTTAATCATTACT) for the liver-specific transcription factor hepatocyte nuclear factor 1 (HNF1). This indicates that the preferential expression from the large surface antigen promoter in the differentiated hepatoma cell lines is probably mediated by HNF1 or an HNF1-related transcription factor.